Gendered environmental pathways to sports injury: insights from retired athletes in the UK high-performance context - Coen, S. E.; Downie, V.; Follett, L.; McCaig, S.; Parsons, J. L. (British Journal of Sports Medicine, 2024)
Objective Women remain at increased risk for some sports injuries, such as anterior cruciate ligament rupture and concussion. This study applied a gendered environmental approach to identify modifiable features of women`s sport environments that may contribute to the gendered patterning of sports injuries. Our objectives were to identify features of gendered environments that mattered in athletes` lived experiences and to trace pathways connecting these features to injury.